2020
DOI: 10.1002/asl.957
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aerosols on lightning activities in central eastern parts of China

Abstract: Time series data of lightning flash rates, aerosol optical depth (AOD), surface relative humidity, potential temperature, and convective available potential energy (CAPE) for 14 consecutive summers (2001-2014) over central eastern parts of China (32.5 -40 N, 100 -120 E) have been analyzed to investigate the impact of aerosol on the lightning flash rate. The Pearson correlation and the partial correlation are used to study the linear correlations between the lightning flash rate and AOD, potential temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 67 publications
5
7
0
Order By: Relevance
“…S1b). However, a lot of extremes are observed in the IGP and WCI which implies that the occurrence of surface heating leads to higher cloud-base heights and more ice-phase hydrometeors, resulting in more lightning in these regions, as also supported from previous studies (Price, 2009;Shindell et al, 2006).…”
Section: Spatial Distribution Of Lightning Propertiessupporting
confidence: 74%
See 1 more Smart Citation
“…S1b). However, a lot of extremes are observed in the IGP and WCI which implies that the occurrence of surface heating leads to higher cloud-base heights and more ice-phase hydrometeors, resulting in more lightning in these regions, as also supported from previous studies (Price, 2009;Shindell et al, 2006).…”
Section: Spatial Distribution Of Lightning Propertiessupporting
confidence: 74%
“…From a climatic point of view, a series of studies in recent years have shown that thunderstorm severity, lightning and its various controlling factors have been increasing prominently in the recent decades, and this has been attributed to the greenhouse-gas-emission-induced surface warming effects both over India and across the globe. A study by Shindell et al (2006) reported that a minimum 10 % increase in lightning activity can be expected for every 1 • C increase due to global warming. Kandalgaonkar et al (2005) suggested that a 1 • C rise in surface temperature over India leads to a 20 %-40 % enhancement in average lightning flash density.…”
Section: Introductionmentioning
confidence: 99%
“…This may be explained by the joint effects of aerosol microphysical effects and aerosol radiative effects under conditions with high aerosol concentration, which may cause the insignificant relationship between lightning activity and aerosols or even suppress the lightning activity. This nonlinear relationship between lightning activity and aerosols was reported in many studies [6,40,59,60].…”
Section: Temporal Variations Of Total Aod and Cg Lightningsupporting
confidence: 58%
“…(Perez-Inverson et al 2021). Other studies showed the positive correlation between relative humidity and lightning activity (Shi et al 2018(Shi et al , 2020. It was reported an increase in relative humidity of about 10% during COVID-19 lockdown period in Chennai (Singh and Tyagi 2021).…”
Section: Resultsmentioning
confidence: 88%